Acetoin Catabolism and Acetylbutanediol Formation by Bacillus pumilus in a Chemically Defined Medium - Xiao, Zijun (Public Library of Science, 2009)
BACKGROUND: Most low molecular diols are highly water-soluble, hygroscopic, and reactive with many organic compounds. In the past decades, microbial research to produce diols, e.g. 1,3-propanediol and 2,3-butanediol, were considerably expanded due to their versatile usages especially in polymer synthesis and as possible alternatives to fossil based feedstocks from the bioconversion of renewable natural resources. This study aimed to provide a new way for bacterial production of an acetylated diol, i.e. acetylbutanediol (ABD, 3,4-dihydroxy-3-methylpentan-2-one), by acetoin metabolism. METHODOLOGY/PRINCIPAL FINDINGS: When Bacillus pumilus ATCC 14884 was aerobically cultured in a chemically defined medium with acetoin as the sole carbon and energy source, ABD was produced and identified by gas chromatography – chemical ionization mass spectrometry and NMR spectroscopy. CONCLUSIONS/SIGNIFICANCE: Although the key enzyme leading to ABD from acetoin has not been identified yet at this stage, this study proposed a new metabolic pathawy to produce ABD in vivo from using renewable resources – in this case acetoin, which could be reproduced from glucose in this study – making it the first facility in the world to prepare this new bio-based diol product.